A unified approach for jointly estimating the business and financial cycle, and the role of financial factors - Tino Berger; Julia Richter; Benjamin Wong (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2021)
We jointly estimate the U.S. business and financial cycle through a unified empirical approach while simultaneously accounting for the role of financial factors. Our approach uses the Beveridge-Nelson decomposition within a medium-scale Bayesian Vector Autore-gression. First, we show, both in reduced form and when we identify a structural financial shock, that variation in financial factors had a larger role post-2000 and a more modest role pre-2000. Our results suggest that the financial sector did play a role in overheatingthe business cycle pre-Great Recession. Second, while we document a positive unconditional correlation between the credit cycle and the output gap, the correlation of the lagged credit cycle and the contemporaneous output gap turns negative when we condition on a financial shock. The sign-switch suggests that the nature of the underlying shocks may be important for understanding the relationship between the business and financial cycles.
Keywords: C18; E51; E32; 330; Business Cycle; Financial Cycle; Financial shocks